National Longitudinal Comparison of Patients Undergoing Surgical Management of Craniosynostosis. Issue 7 (October 2018) - Wu, Robin T.; Shultz, Blake N.; Gabrick, Kyle S.; Abraham, Paul F.; Cabrejo, Raysa; Persing, John A.; Alperovich, Michael
Abstract : Purpose: Limited cross-institutional studies compare strip craniectomy versus cranial vault remodeling (CVR) for craniosynostosis management. Given competing surgical preferences, the authors conducted a large-scale analysis of socioeconomic differences, costs, and complications between treatment options. Methods: Nonsyndromic craniosynostosis patients receiving strip craniectomies or CVR were identified in the Kids' Inpatient Database for years 2000 to 2009. Demographics, socioeconomic background, hospital characteristics, charge, and outcomes were tabulated. Univariate and multivariate analyses were performed for comparison. Results: Two hundred fifty-one strip craniectomies and 1811 CVR patients were captured. Significantly more strip craniectomy patients were White while more CVR patients were Hispanic or Black ( P  < 0.0001). Strip craniectomy patients more often had private insurance and CVR patients had Medicaid ( P  < 0.0001). Over time, CVR trended toward treating a higher proportion of Hispanic and Medicaid patients ( P  = 0.036). Peri-operative charges associated with CVR were $27, 962 more than strip craniectomies, and $11, 001 after controlling for patient payer, income, bedsize, and length of stay ( P  < 0.0001). Strip craniectomies were performed more frequently in the West and Midwest, while CVR were more common in the South ( P  = 0.001). Length of stay was not significant. Postsurgical complications were largely equivocal; CVR was associated with increased accidental puncture ( P  = 0.025) and serum transfusion ( P  = 0.002). Conclusion: Our national longitudinal comparison demonstrates widening socioeconomic disparities between strip craniectomy and CVR patients. Cranial vault remodeling is more commonly performed in underrepresented minorities and patients with Medicaid, while strip craniectomy is common in the White population and patients with private insurance. While hospital charges and complications were higher among CVR, differences were smaller than expected.